The research on business concentration in Lithuanian economy - Ginevičius, Romualdas; Krivka, Algirdas (Business: Theory and Practice, 2009)
The trend of growing business concentration has become common for the process of developing of Lithuanian economy nowadays; besides, high concentration in certain industries could be related to the former state monopoly privatization. A market or an industry, dominated by several producers or sellers, is considered to be oligopoly. The economists of the neo-classical school, accompanied by the scholars of modern microeconomics and industrial organization, associate oligopoly with a threat of cartels or other agreements on coordination of behaviour, improper use of the dominating position, consumer ineffective equilibrium even in case of fair competition. The article presents the complex research on business concentration in the main sectors of Lithuanian industry, trade and services in an attempt to identify oligopolistic industries and evaluate their weight in the economy of the state. The evaluation of concentration is quantitative: the calculations are made by applying the concentration and the Herfindahl-Hirschman ratios – the ones that are most commonly used in similar researches. The 4-digit (detailed) classification of economic activities, approved by the Department of Statistics to the Government of the Republic of Lithuania, is used to distinguish between industries. Published economic activity level statistics for the calendar year 2006 together with the data on the sales of the largest enterprises in potentially concentrated industries are involved in the research.Article in Lithuanian.Verslo koncentracijos Lietuvos ekonomikoje tyrimasSantrauka. Šiuolaikinei Lietuvos ekonomikai būdingos verslo koncentracijos augimo tendencijos, be to, atskirose ūkio šakose aukšta verslo koncentracija susidarė privatizuojant valstybės monopoliui priskirtinų ūkinių veiklų įmones. Rinkoje arba ūkio šakoje  dominuojant  keliems  gamintojams  (pardavėjams),  ji  laikytina  oligopoline. oligopolija  neoklasikinių  ekonomistų,  taip pat šiuolaikinių mikroekonomikos ir industrinės organizacijos mokslininkų siejama su kartelinių susitarimų ar kitokio veiksmų derinimo grėsme, piktnaudžiavimu dominuojančia padėtimi, vartotojų atžvilgiu neefektyvia pusiausvyra net ir vykstant sąžiningai konkurencijai. Straipsnyje atliekamas verslo koncentracijos pagrindiniuose Lietuvos pramonės, prekybos ir paslaugų sektoriuose kompleksinis tyrimas išskiriant oligopolines ūkio šakas ir nustatant jų dalį šalies ekonomikoje. Koncentracijos lygis nustatomas kiekybiškai,  pasitelkus  tokio  pobūdžio  tyrimams  plačiausiai  naudojamus  koncentracijos  ir  Herfindahl-Hirschman  indeksus, juos pritaikant Statistikos departamento prie Lietuvos Respublikos Vyriausybės ekonominės veiklos rūšių klasifikatoriaus 4-ių ženklų lygioms (detaliosioms) ekonominės veiklos rūšims. Tyrime naudojami minėtos institucijos viešai skelbiami 2006 metų ekonominės veiklos rūšių suvestiniai statistiniai duomenys, taip pat vykdant tyrimą atrinktų potencialiai koncentruotų ūkio šakų stambiausių įmonių pardavimo pajamų duomenys.Reikšminiai  žodžiai:  rinkos  struktūra,  oligopolija,  ūkio  šaka,  koncentracija,  koncentracijos  laipsnis,  Herfindahl-Hirschman indeksas.First published online: 22 Sep 2009